SARS-CoV-2 infection in patients with primary Sjögren syndrome: characterization and outcomes of 51 patients. (14th December 2020) - Brito-Zerón, Pilar; Melchor, Sheila; Seror, Raphaèle; Priori, Roberta; Solans, Roser; Kostov, Belchin; Baldini, Chiara; Carubbi, Francesco; Callejas, Jose Luis; Guisado-Vasco, Pablo; Hernández-Molina, Gabriela; Pasoto, Sandra G; et al.
Abstract: Objective: To analyse the prognosis and outcomes of SARS-CoV-2 infection in patients with primary SS. Methods: We searched for patients with primary SS presenting with SARS-CoV-2 infection (defined following and according to the European Centre for Disease Prevention and Control guidelines) among those included in the Big Data Sjögren Registry, an international, multicentre registry of patients diagnosed according to the 2002/2016 classification criteria. Results: A total of 51 patients were included in the study (46 women, mean age at diagnosis of infection of 60 years). According to the number of patients with primary SS evaluated in the Registry ( n  = 8211), the estimated frequency of SARS-CoV-2 infection was 0.62% (95% CI 0.44, 0.80). All but two presented with symptoms suggestive of COVID-19, including fever (82%), cough (57%), dyspnoea (39%), fatigue/myalgias (27%) and diarrhoea (24%), and the most frequent abnormalities included raised lactate dehydrogenase (LDH) (88%), CRP (81%) and D-dimer (82%) values, and lymphopenia (70%). Infection was managed at home in 26 (51%) cases and 25 (49%) required hospitalization (five required admission to ICU, four died). Compared with patients managed at home, those requiring hospitalization had higher odds of having lymphopenia as laboratory abnormality (adjusted OR 21.22, 95% CI 2.39, 524.09). Patients with comorbidities had an older age (adjusted OR 1.05, 95% CI 1.00, 1.11) and showed a risk for hospital admission six times higher than those without (adjusted OR 6.01, 95% CI 1.72, 23.51) in the multivariate analysis. Conclusion: Baseline comorbidities were a key risk factor for a more complicated COVID-19 in patients with primary SS, with higher rates of hospitalization and poor outcomes in comparison with patients without comorbidities.